Parental strategies in supporting children's learning process in the digital era - Tria Silvia Manurung; Nur Wahyuni (Sean Institute, 2024)
Education in the digital era is an era where education must integrate communication and information technology into all subjects. The increasingly rapid development of technology in the current era has resulted in the emergence of positive and negative things for humans. The development of digital technology in the current era has resulted in the role of parents in educating their children also changing. Parental involvement in supervising children's education in the digital era is very important because it will really help children in the success of their children's education in the digital era. This research aims to identify and analyze the strategies used by parents to support their children's learning process in the digital era. The method used in this research is a qualitative approach in document study. The document study in question is a study that searches for literature in accordance with study materials such as books, articles, the internet and so on. (Long in Marani, 2017). The methods for collecting data include; First, carry out a literature review that is appropriate to the material being researched. Then these materials are collected. Second, after obtaining the data, the author carried out an analysis based on his understanding using descriptive methods.